18F-FDG PET / CT findings of Rosai Dorfman Disease withdiffuse extranodal involvement - FİLİZOĞLU, NUH; KESİM, SELİN; ENGÜR, CEREN ÖZGE; ÖZGÜVEN, SALİH; ÖNEŞ, TUNÇ; TUROĞLU, HALİL TURGUT; ERDİL, TANJU YUSUF (My University, 2020)
Aim/Introduction: Rosai Dorfman disease (RDD) is a rare benign disease characterized by permanent massive lymphadenopathy mimicking malignant tumors. Extranodal involvement, including the skin, upper respiratory tract, salivary gland, bone, central nervous system and rarely kidneys, may occur in approximately 43% of patients. Although RDD can usually recover spontaneously, it may persist in some patients and mimic lymphoproliferative disorders clinically and visually. We present the 18F-FDG PET / CT findings of the patient with RDD with diffuse extranodal involvement. Materials and Methods: An 18F-FDG PET / CT examination was performed to investigate malignancy in a 57-year-old male patient with multiple cervical lymph nodes. Results: 18F-FDG PET / CT demonstrated 2.5 cm sized intense hypermetabolic lymph nodes in the bilateral cervical chain. Intense hypermetabolic soft tissue density lesions were observed in the subcutaneous fatty plans of the T12 vertebra left posterolateral section and the right lower quadrant of the abdomen. 12 mm sized mild hypermetabolic soft tissue density nodular lesion was seen in the right adrenal gland medial crust and 3x2.5 cm sized mild hypermetabolic soft tissue density nodular lesion was found in the left adrenal gland corpus. In the skeletal system, intense hypermetabolic lytic lesions compatible with metastasis were observed in the left occipital condyle, the posterior elements of the T6 vertebra, the C1 vertebra transvers process, the posterior part of the right acetabulum and the posterior part of the right iliac bone. Excisional biopsy was performed on the lymph node in the submandibular area and the lesion observed in the subcutaneous fatty plan in the right lower quadrant of the abdomen and the histopathology was found compatible with Rosai Dorfman disease. Conclusion: RDD, first described by Rosai and Dorfman in 1969, is a rare benign lymphoproliferative disease. RDD is usually manifested by cervical lymphadenopathy and typically mimics lymphoma. Diseases such as lymphoma, tuberculosis, sarcoidosis, reactive hyperplasia and nasopharyngeal carcinoma can be considered in the differential diagnosis. Extranodal disease is observed in approximately 43% of cases, most commonly in the skin, nasal cavity, eyes and bone. Although Rosai-Dorfman disease is usually self-limited, patients with extranodal involvement may have a more fulminant course and need active treatment. Since lesions show increased FDG uptake, 18F-FDG PET-CT may be useful in determining the extent of the disease, including lymph node involvement. Therefore, the present case emphasized the importance of 18F-FDG PET-CT scan in the diagnosis, staging and treatment selection of the disease. References: None